The +Plus Series: Microsoft (tm) Outlook 2003 (+Plus Series) - L.Nielsen Brenda (McGraw -Hill, 2004)
Thousands of learners have asked for high quality materials that focus on technologies that go beyond core applications of Microsoft Office. McGraw-Hill Technology Education has answered these requests with 4 new titles making up the +Plus Series. This books were designed to stand alone as primary texts or to supplement instruction in core courses. The +Plus Series books are brief, easy to use, and less expensive than primary textbooks.